2013
DOI: 10.4209/aaqr.2012.10.0277
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Fires and Their Potential Impacts on Regional Air Quality over China

Abstract: The potential impacts of agricultural fires (agri-fires) on regional air quality over China were examined using active fire products derived from satellite remote sensing and air mass trajectory modeling from 2009 to 2010. Agri-fires were found in most administrative areas. More than 80% of the agri-fires were in the heartlands of agricultural regions such as Anhui, Jiangsu, Shandong and Henan Provinces. Agri-fires had a seasonal pattern, with two distinct peaks in summer and autumn harvest periods, especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…Very few active fires occurred in Northeast China, region # 3 (120°-130°E and 42°-50°N). Burning of crop residues in Northeast China was frequently detected in early spring and late fall, the harvest season of crops (Xia et al, 2013;Zha et al, 2013). In June, a few active fire points were only observed in late June and most of fires occured in region #2 (the maximum active fire count of 185 occuring on June 28).…”
Section: Resultsmentioning
confidence: 99%
“…Very few active fires occurred in Northeast China, region # 3 (120°-130°E and 42°-50°N). Burning of crop residues in Northeast China was frequently detected in early spring and late fall, the harvest season of crops (Xia et al, 2013;Zha et al, 2013). In June, a few active fire points were only observed in late June and most of fires occured in region #2 (the maximum active fire count of 185 occuring on June 28).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies also demonstrated that the North China Plain, Northeastern China and South China were the most important contributors to crop open burning in fields [17]. More than 80% of the agricultural burnings were in the agricultural regions, such as Anhui, Jiangsu, Shandong and Henan Provinces [10]. The temporal pattern of crop open burning is significantly associated with local sowing and harvest timing.…”
Section: Agricultural Open Field Biomass Burning In Chinamentioning
confidence: 91%
“…Emissions of gaseous pollutants and aerosol particles from biomass burning have a significant impact on air quality, human health, and climate [4,5] and significantly contribute to the tropospheric radiation budgets on local, regional and even global scales [6][7][8]. Due to the substantial effect of biomass burning on air quality and climate, biomass burning emissions and their impact on air quality has been extensively studied in China through ground observation [4,9], satellite remote sensing [10,11], and model simulation [12,13]. There are three approaches to estimating biomass burning emissions: (1) combining statistical data (e.g., product of crop production, residue-to-production ratio, dry matter-to-crop residue ratio, the percentage of dry matter burned in fields, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In view of the important impacts on global climate and regional air quality, the scientific community has developed a number of operational fire products based on the detection of thermal anomalies (i.e., active fires, abbreviated to AF) and land surface changes (i.e., burned areas, abbreviated to BA). The AF products provide key response information about the locations of fires that are burning when the satellite passes by (Chalbot et al, 2013;Zha et al, 2013). The satellitederived BA products are key data that are used to support the global greenhouse gases (GHGs) emissions inventory and climate modeling.…”
Section: Introductionmentioning
confidence: 99%